Assessment of Clinic-Based Growth Monitoring and Promotion in the Accra Metropolitan Area of Ghana - Gyampoh, S. (University of Ghana, 2012)
Growth Monitoring and Promotion (GMP) is a public health intervention which makes use of frequent assessment of the growth of children under five years. The programme enables health workers to early detect growth failure and take corrective actions through improvements in feeding and care practices. Despite evidence that most caregivers in Ghana have contact with GMP through monthly child welfare clinics (CWC), child feeding practices remain sub-optimal and child undernutrition persists. The study assessed the implementation of GMP in Ghana and the relationship between caregiver exposure to GMP and child feeding knowledge and practices, the nutritional status of their children and knowledge of GMP. The study was cross-sectional, involving 206 caregiver-child pairs attending child welfare clinics (CWC) and 17 health workers providing GMP services at the CWC in the Accra Metropolitan Area (AMA). Observation checklists were used to assess health worker implementation of GMP activities for caregiver-child pairs. Child health records provided data on caregiver attendance. Structured questionnaires were used to collect data on caregiver-child pair characteristics, child feeding knowledge and practices, and knowledge of GMP activities. Weights and heights of participating children were measured to determine nutritional status. Structured questionnaires were also used to collect data on health worker knowledge of recommended child feeding and GMP activities. Comprehension of the child growth chart by caregivers and health workers was assessed using sample charts. Recording of child weights on the appropriate growth chart for boys and girls were correctly done in over 97% of children. However, over 50% of children did not have all their monthly weight points connected on the growth chart to show the trend of growth. More than 60% of caregiver-child pairs in the study received no growth promotion education and only about 3% of children experiencing faltering growth in two consecutive months were referred for appropriate intervention as prescribed in the health records book by the Ghana Health Service. Caregivers who had not missed any CWC attendance had significantly better growth chart comprehension scores (p=0.026). Nutritional status of children and caregiver knowledge of recommended child feeding was not significantly associated with CWC attendance (p= 0.707; p=0.136). The relationship between caregiver CWC attendance and child feeding practices was also not found to be significant. Overall, over half of the percentage of health workers in the study had poor knowledge scores of recommended child feeding practices and the growth chart. Generally most health workers knew recommended child feeding practices and GMP activities, however some health workers could not adequately indicate recommended actions for particular growth trends on the growth chart. Data recording and charting practices were appropriately carried with the exception of plotting of child weights. Growth promotion education was also observed to be inadequately carried out. Among caregivers breastfeeding practices were well practiced while complementary feeding practices were suboptimal. Not missing any CWC was not significantly associated good feeding knowledge and practice scores and child nutritional status as with good growth chart comprehension. For GMP to achieve its goals, it is necessary for the government/GHS to routinely train health workers on GMP. It is also equally essential to provide the needed logistics and improve the organisation of CWC in order to reduce health worker workload and enhance effectiveness.
Thesis (MPHIL)-University of Ghana, 2012